Dual Effect of Azospirillum Exopolysaccharides (EPS) on the Enhancement of Plant Growth and Biocontrol of Blast (Pyricularia oryzae) Disease in Upland Rice (var. ASD-19) - r, J. Uma Sankari*, S. Dinakar, and C. Seka (Journal of Phytology, 2011)
The dual effect of exopolysaccharides of Azospirillum isolates viz., A-17, A-18, A-26 and A-37 and certain ISR inducing chemicals viz., Salicylic acid, Jasmonic acid and Azibenzolar on the enhancement of plant growth and bio-control against blast disease in upland rice crop was studied under in-vitro condition. It was observed that the application of EPS, collected from Azospirillum isolates, augmented the height of rice plant and reduced the blast disease incidence in upland rice to a higher level when compared to the application of ISR inducing chemicals alone. Eventhough,Ã‚Â  the application of ISR inducing chemicals was found to reduce the blast disease incidence, as in the case of purified EPS application of Azospirillum isolates, but did not augment the growth of rice plant and clearly revealed the absence of phytostimulatory activities of ISR inducing chemicals.The study on the optimization of different concentrations of purified EPS viz., 100, 200, 300 ppm on the blast disease incidence of rice revealed that the application of the same at 200 ppm concentration could effectively controlled the disease incidence to a higher level when compared to other concentration. The results of the present study clearly revealed the dual effect of Azospirillum EPS on the enhancement of host plant growth as well as the bio-control against Pyricularia oryzae whereas the application of ISR inducing chemicals confined with reduction in blast disease incidence alone. Moreover, the Azospirillum EPS at a concentration of 200 ppm level could be optimized as effective one for the control of blast disease in upland rice.